Escolarização de elites na perspectiva das famílias - Torres, Julio Cesar [UNESP]; Pirani, Mário Luiz (My University, 2014)
We investigated strategies for children education of academic elites. Our study had as basis researches done in Brazil about the scholarization of elites’ groups during the last two decades. The theorical referential for the definition and the problematization of our object of study was based on Almeida and Nogueira’s works (2002), Bourdieu and Passeron (1975), Brandão and Lellis (2003), Busetto (2006), Lacerda and Carvalho (2007) and Nogueira (1998; 2002; 2005). We developed desk research on the pedagogical proposals of a high school in São Paulo state, its image among the society analyzed through advertising material and the application of semi-structured interviews with six families. The results shows that not only the educational but also the families goals in maintaining privileged positions in terms of children’s admission to universities and courses of high prestige, and the perpetuation of the condition in belonging to an elite group.

Neste estudo são investigadas estratégias de escolarização de filhos de elites acadêmicas. O referencial teórico para a problematização do objeto está apoiado em Nogueira (1998, 2005), Bourdieu (1997, 1998), Busetto (2006), Lacerda e Carvalho (2007). Procedeu-se à pesquisa sobre as propostas pedagógicas de uma escola de ensino médio privada de um município do interior paulista, o levantamento de sua imagem junto à sociedade veiculada por mensagens publicitárias e a realização de entrevistas semiestruturadas com seis famílias que possuem filhos matriculados. Os resultados apontam haver indícios que relacionam os objetivos educacionais das famílias com as intenções da escola na manutenção de posições privilegiadas no quesito de aprovação em universidades e cursos de alto prestígio social, além da perpetuação da condição de pertencimento a uma elite.
Elite scholarization in the perspective of the families
Keywords: Contratos de sucesso escolar; Escolarização de elites; Reprodução social; School success contracts; Education of elites; Social reproduction